(untitled) (Ameghiniana, 2014)
A description of some fossil gymnospermous wood fragments from the La Ternera Formation at the Quebrada El Carbon locality, northern Chile, is presented herein. One of the pieces of wood has a lobulate pith, primary xylem and secondary xylem with marked grawth rings and is assigned to Lobatoxylon kamthiensis (Prasad) n. combo The genus Lobatoxylon has been used instead of Trigonomyelon which is considered invalid. Only secondary xylem has been preserved in the second specimen, which is assigned to Araucarioxylon semibiseriatum Pant and Singh. Both taxa are reported from Chile for the first time.